Pemerolehan AL-AMR dalam ayat nominatif bahasa arab pelajar UiTM Perlis - Ummi Syarah Ismail (Tanjong Malim, 2019)
Pemerolehan AL-AMR dalam ayat nominatif bahasa arab pelajar UiTM Perlis by Ummi Syarah Ismail